Prevent Workers from Injuries in the Brewing Company via Using Digital Human Modelling Technology - Xiaoxu Ji; Ranuki O. Hettiarachchige; Alexa L. E. Littman; Nicole L. Lavery; Davide Piovesan (Applied Sciences, 2023)
A large percentage of musculoskeletal disorder cases occur in brewing companies. The aim of this research study is to evaluate the risk of injuries for workers in the local brewing industry by integrating the actual human motion, which was captured by the Xsens MVN Awinda motion tracking system, with the JACK Siemens ergonomics tools. This proposed fusion technology greatly overcomes the time-consuming issue in the traditionally full-body simulation and the posture sensitivity issue in the current digital human modelling (DHM) technology. In this study, the subjects performed a series of daily lifting tasks utilizing 72 kg kegs. The forces exerted on the lower back of brewery workers were fully analyzed. The maximum load applied on the hands for each of the tasks was also estimated to prevent workers from injuries. Additionally, the key factors that highly correlate to lower back injuries were emphasized. Due to the heavy load applied by the kegs, large spinal forces were exerted on the lower back of workers. Moreover, reducing trunk and hip flexion is also important to prevent workers from injuries. The results of this study can greatly improve the implementation of training techniques, environmental modifications, and assistive device design, which aim to eliminate injury risk and increase the productivity of workers within the breweries.